Radial electromagnetic force and vibration in synchronous reluctance motors with asymmetric rotor structures. Issue 9 (2nd April 2021) - Lin, Yingqian; Sun, Yi; Wang, Yunchong; Cai, Shun; Shen, Jian‐Xin
Abstract: Asymmetrical rotor topologies were previously proposed for synchronous reluctance motors (SynRM) to reduce the torque ripple. However, potential negative effect of these topologies on mechanical vibration, which is often serious in SynRM, was hardly studied and such an effect is investigated here. An analytical model is established, through which the spatial orders of the radial electromagnetic force with various rotor topologies are derived, and the relationship of the peak frequencies and the corresponding spatial orders in the radial electromagnetic force is revealed. It is shown that some asymmetric rotor topologies will reduce the order of the lowest spatial harmonic for the radial electromagnetic force, and consequently increase the vibration. Finite element analysis and experiments demonstrate the same results. Finally, a specific rotor topology with asymmetry about both d ‐axis and q ‐axis is recommended, which can reduce the torque ripple, but would not deteriorate the radial electromagnetic force and vibration.